Peran Orang Tua Peran Orang Tua Dalam Perkembangan Kognitif Anak Usia 4 -5 Tahun Di Ra Nawa Kartika Dawu Masa Pandemi Covid-19 : Perkembangan Kognitif pada Masa Pandemi - Eko Prasetiyo; Widyawati Widyawati (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
Cognitive development of early childhood cannot be separated from the role of parents and the family environment. In the family environment, children are encouraged to explore, learn and appreciate human values, religion, norms and knowledge. Children are the best imitators of the attitude of their parents, because every child's activity is related to their parents. The COVID-19 pandemic that hit Indonesia had a significant impact on all aspects of people's lives. The education aspect is no exception. This requires the government to implement a new pattern of life. Before Covid-19, learning was done face-to-face, so when a pandemic like this occurs, learning is done using an online system (on a network). This habituation pattern makes children's activities 100% at home, therefore the role of parents in child development is needed, especially cognitive development. The results showed that (1) the contribution of parents as an extension of the teacher at school in assisting children in learning at home. (2) The involvement of parents in creating a learning atmosphere at home so as to improve children's cognitive development. Key Words: Pandemic, the role of parents, cognitive, children